Neuroplasticity in adult human visual cortex. (May 2020) - Castaldi, Elisa; Lunghi, Claudia; Morrone, Maria Concetta
Highlights: Short-term monocular deprivation triggers homeostatic plasticity in adult humans. Physical activity and inverse occlusion promote visual recovery in amblyopic adults. Cross-modal plasticity and functional repurposing occur in late-blind individuals. Sight restoration in late-blind adults promotes early visual cortex re-organization. The adult visual system retains residual plasticity well after the critical period. Abstract: Between 1-5:100 people worldwide have never experienced normotypic vision due to a condition called amblyopia, and about 1:4000 suffer from inherited retinal dystrophies that progressively lead to blindness. While a wide range of technologies and therapies are being developed to restore vision, a fundamental question still remains unanswered: would the adult visual brain retain a sufficient plastic potential to learn how to 'see' after a prolonged period of abnormal visual experience? In this review we summarize studies showing that the visual brain of sighted adults retains a type of developmental plasticity, called homeostatic plasticity, and this property has been recently exploited successfully for adult amblyopia recovery. Next, we discuss how the brain circuits reorganize when blindness occurs and when visual stimulation is partially restored by means of a 'bionic eye' in late blind adults with Retinitis Pigmentosa. The primary visual cortex in these patients slowly became activated by the artificial visual stimulation, indicating that sight restoration therapies can rely on a considerable degree of spared plasticity in adulthood.